Current status of indications, timing, management, complications, and outcomes of tracheostomy in traumatic brain injury patients (2020)
Tracheostomy is the commonest bedside surgical procedure performed on patients needing mechanical ventilation with traumatic brain injury (TBI). The researchers made an effort to organize a narrative review of the indications, timing, management, complications, and outcomes of tracheostomy in relation to neuronal and brain-injured patients following TBI. The study observations were collated from the published literature, namely original articles, book chapters, case series, randomized studies, systematic reviews, and review articles. Information sorting was restricted to tracheostomy and its association with TBI. Care was taken to review the correlation of tracheostomy with clinical correlates including indications, scheduling, interventions, prognosis, and complications of the patients suffering from mild, moderate and severe TBIs using Glasgow Coma Scale, Glasgow Outcome Scale, intraclass correlation coefficient, and other internationally acclaimed outcome scales. Tracheostomy is needed to overcome airway obstruction, prolonged respiratory failure and as indispensable component of mechanical ventilation due to diverse reasons in intensive care unit. Researchers are divided over early tracheostomy or late tracheostomy from days to weeks. The conventional classic surgical technique of tracheostomy has been superseded by percutaneous techniques by being less invasive with lesser complications, classified into early and late complications that may be life threatening. Additional studies have to be conducted to validate and streamline varied observations to frame evidence-based practice for successful weaning and decannulation. Tracheostomy is a safer option in critically ill TBI patients for which a universally accepted protocol for tracheostomy is needed that can help to optimize indications and outcomes.